Strengthening Teachers’ Competence in Developing Diagnostics Tests for Learning - Erlin Eveline; Herman S. Wattimena; Heppy Sapulate; John Rafafy Batlolona; Gazali Rachman; David Tuhurima; Cicylia Triratna Kereh; Marasi Bless Suryan; Anastasija Limba; Juliana Nirahua (Pascasarjana Universitas Mataram, 2025)
The purpose of this community service is to strengthening teachers’ competence about diagnostics test for deep learning approach. The community service is conducted to address the challenges of Indonesia’s new curriculum policy about deep learning based on meaningful learning. The implementation methods include opening, materials explanation, discussion, assessment, and closing. Assessment was conducted by questionnaire and test. The result of the assessment from the questionnaire shows positive responses from teachers. The average scores each statement ranges from 82% to 97%. It indicates a high level of participant satisfaction with the community service. The teachers gained strengthened knowledge about deep learning and the development of diagnostic instruments. The results indicate that the teachers found this community service beneficial, relevant to classroom needs, and applicable in teaching. In addition, most teachers were aware of diagnostic instruments (61,1%), but only a few teachers had ever developed them (5.6%) or conducted them in their classroom (11.1%). It shows that the implementation of the diagnostics test is still limited before conducting the training. The result of the assessment from the test shows the mean score obtained by the teachers was 86,67. A total of 16 out of 18 teachers (88,9%) scored 80, which is categorized as good, while 2 teachers scored below 80. Thus, the percentage of teachers exceeded the predetermined achievement indicator of 70%. It is hope that this activity can help teachers in supporting deep learning approach at classroom.